Experienced ESD-schoolteachers’ teaching – an issue of complexity - Sund, Per (Environmental Education Research, 2015)
In educational settings, sustainable development (SD) is often handled with the aim of reducing the contested aspects of the concept. Issues like trade, conservation, public health and international relations are often presented in a simplified way so that they are easier for students to grasp. However, in education, this tendency to simplify sustainability issues can be a disadvantage. This study explores how Swedish upper secondary school teachers’ education for sustainable development (ESD) in award-winning ‘ESD-schools’ supports students to become informed and autonomous democratic citizens by appreciating the complexity of the concept of SD. This empirical study is part of a larger research project studying progressive upper secondary schools and is a development of earlier research on teachers’ starting points for long-term purposes beyond the teaching – which we have termed objects of responsibility. In interviews of five teachers from two schools, experienced in ESD issues and working in teacher teams, an interesting commonality in their arguments for teaching sustainability emerged during the analytical process. The implications of the study’s results are important for EE/ESD research into teaching continuity as well as for teachers in practice.